1997
DOI: 10.1023/a:1006512018609
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Integrins with the alphav subunit are involved in cell adhesion and cellular signaling. Some alphav integrins have been associated with tumor progression and dissemination. The objective of this study was to assess the contribution of alphav integrins to the adhesive and migratory behavior of cells derived from breast carcinoma (BCA). The expression and function of alphav integrins was characterized in three BCA cell lines which exhibit different metastatic potentials. These include MCF-7 cells which metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(34 citation statements)
references
References 51 publications
6
27
0
1
Order By: Relevance
“…Previous studies have demonstrated that MDA-MB-231 cells attach equally well on several ECM proteins, such as type I collagen, ®bronectin, laminin-1 and vitronectin (Lichtner et al, 1998;Lundstrom et al, 1998;van der Pluijm et al, 1997;Wong et al, 1998), and we found the same here. Also of note, no di erences in cell survival were observed when MDA-MB-231 cells were plated on di erent matrix substrates or on the non-integrin ligand polylysine for extended periods of time in the absence of any drug treatment (not shown).…”
Section: Resultssupporting
confidence: 88%
“…Previous studies have demonstrated that MDA-MB-231 cells attach equally well on several ECM proteins, such as type I collagen, ®bronectin, laminin-1 and vitronectin (Lichtner et al, 1998;Lundstrom et al, 1998;van der Pluijm et al, 1997;Wong et al, 1998), and we found the same here. Also of note, no di erences in cell survival were observed when MDA-MB-231 cells were plated on di erent matrix substrates or on the non-integrin ligand polylysine for extended periods of time in the absence of any drug treatment (not shown).…”
Section: Resultssupporting
confidence: 88%
“…The former use the laminin receptor ␣ 6 ␤ 1 , whereas the latter primarily use the vitronectin receptor ␣ v ␤ 3 . This result extends previous results demonstrating the avid attachment of breast cells to vitronectin substrates (44,65). Breast cells have a large variety of integrin dimers on their surfaces for binding to matrix components (43), but primarily utilize ␣ v ␤ 1 , ␣ v ␤ 3 , and ␣ v ␤ 5 for vitronectin (66).…”
Section: Discussionsupporting
confidence: 87%
“…6b). This is consistent with the report that the expression of ␤3 in MCF-7 cells is very low (40). Our results suggest that ␣6␤4 integrin plays a major role in NRG signaling in MCF-7 cells.…”
Section: Nrg1 Induces Co-precipitation Of Integrins and Erbb3 Whereasupporting
confidence: 94%